Impact of early enteral nutrition on the prognosis of mechanically ventilated patients with chronic obstructive pulmonary disease: a retrospective cohort study based on the MIMIC-IV Database - Ouyang, Lamei; Wang, Canmin; Song, Yunfeng (Frontiers in Nutrition, 2025)
BackgroundWhile early enteral nutrition (EN) is recommended for critically ill patients, its specific impact on mechanically ventilated chronic obstructive pulmonary disease (COPD) patients remains uncertain.MethodsWe analyzed data extracted from the MIMIC-IV 3.0 database, focusing on patients with COPD who received invasive mechanical ventilation. The cohort was stratified into two groups: the early EN group (EEN, EN initiated within 48 h of ICU admission), and the delayed EN group (DEN, EN initiated after 48 h of ICU admission). Propensity score matching (PSM) was employed to balance baseline characteristics between the groups, enabling a comparative analysis of clinical outcomes.ResultsAmong 1,052 patients, 513 (48.76%) were in the early EN group and 539 (51.24%) were in the delayed EN group. After PSM, no statistically significant differences were observed in 28-day mortality (30.51% vs. 32.82%, p = 0.488), ICU mortality (17.18% vs. 21.28%, p = 0.146), or 60-day mortality (38.21% vs. 39.74%, p = 0.660). Similarly, the incidence of ventilator-associated pneumonia (VAP) did not differ significantly between the EEN and DEN groups (20.77% vs. 23.33%, p = 0.388). However, the EEN group exhibited a significantly shorter duration of mechanical ventilation (127.50 vs. 137.94 h, p = 0.023), reduced ICU length of stay (9.08 vs. 10.07 days, p < 0.01) and total hospitalization (14.64 vs. 16.63 days, p = 0.001). Additionally, subgroup analysis revealed that EEN significantly reduced 28-day mortality in patients with PaO2/FiO2 >200 (OR = 0.626, 95% CI: 0.414–0.943; p = 0.026).ConclusionAlthough early EN did not significantly improve overall mortality, it effectively decreased ventilation duration and hospital stays and demonstrated potential survival benefits for patients with better oxygenation. These findings provide critical evidence for optimizing nutritional support strategies in mechanically ventilated COPD patients.